Asset pricing with a bank risk factor - Pereira, João Pedro (2019)
Funding agency: Portuguese National Funds through FCT - Fundacao para a Ciencia e Tecnologia (grant nr. UID/ECO/00124/2013, PTDC/EGE-GES/119274/2010)